KEPASTIAN HUKUM PENGUASAAN TANAH ADAT OLEH DESA PAKRAMAN TUSAN BANJARANGKAN - A.A. Mas Adi Trinaya D (Kerta Dyatmika, 2019)
The settlement of village yard disputes the village head and customary bendesa play a very important role. Village Head and Bendesa Adat as the interpreter of peace is very reasonable, still included within the boundaries of its duty to make the people of their village to live in peace and peace. In view of the root of the problem, a dispute or violation of the law may be a case of pure custom, a non-custom case, or a mixed case (custom case + non-adat). Included in the category of indigenous cases are disputes whose objects are customary issues or violations which according to local dresta are disgraceful acts but not regulated in the laws and regulations of the State for example are disputes / violations relating to fathers (customary duties), Prohibition of burying corpses in setra, kasepekang case, lokika sanggraha, wrong timpal and others Thus legal certainty of customary land tenure in pakraman village is important to do because nowadays there are often conflicts of villagers pakraman back ground about the land starting from the land of inheritance, land Village yard and village wasteland (AYDS). Above the above, the authors are interested to conduct research by taking the title: "Legal Certainty of Land Ownership Adat By Pakraman Tusan Village Banjarangkan". Based on the above background, can be raised several issues as follows: How is the legal basis of land ownership of Adat by Desa Pakraman Banjarangkan Klungkung And How are the factors inhibiting legal certainty of Indigenous land ownership by Desa Pakraman Banjarangkan Klungkung. The type of research used is the study of Empirical law because in this study besides based on existing theories then also compared the theories with the existing situation in the Village Pakraman Tusan Banjarangkan Klungkung. From the discussion can be drawn the following conclusions: The legal basis of customary land tenure by the Village Pakraman is Law No. 23 of 2014 and Bylaw Bali. 3 Year 2001 and awig-awig Desa Pakraman Tusan Banjarangkan Klungkung Krama village which occupies the reef land of the village, has a strong position against its existence in traditional village, both seen from the rights and obligations. The duties include tedun mebanjar, paying rural / village fees, ngayahang village reef land, mutual assistance and the factors inhibiting legal certainty of land tenure by the village of Pakraman Tusan Banjarangkan Klungkung, among others: ground pipil / girik not clear, the existence of customary village krama Who are in other pakraman village area and others.Keywords : Legal Certainty, Customary Land and Pakraman Village